Googling NDIS: evaluating the quality of online information about the National Disability Insurance Scheme for caregivers of deaf children. (2nd January 2017) - Simpson, Andrea; Baldwin, Elizabeth Margaret
ABSTRACT: This study sought to analyze and evaluate the accessibility, availability and quality of online information regarding the National Disability Insurance Scheme (NDIS) and hearing loss. The most common search engine keyword terms a caregiver may enter when conducting a web search was determined using a keyword search tool. The top websites linked with each keyword term were then evaluated using a subjective quality rating tool. It was found that only 8% of the websites evaluated referred users directly to the NDIS. The majority of websites (70%) scored in the fair range for overall quality with 15% of websites scoring poorly and 15% of websites scoring highly. However, the hierarchy in which websites were presented on Google when a search string was typed into the search bar was not necessarily associated with the highest quality website appearing first. Overall, whilst the quality of information regarding the NDIS was of a fair quality, the accessibility to this information by caregivers was found to be poor.